Schooling from home: millennial moms family communication and media uses in COVID-19 - Setyastuti, Yuanita; Suminar, Jenny Ratna; Hadisiwi, Purwanti; Zubair, Feliza (Jurnal Studi Komunikasi, 2021)
This study aimed to determine family communication based on satisfaction with the uses of new media technology by millennial mothers and teachers in children studying from home during the Covid-19 pandemic. This research was conducted qualitatively through online interviews at the beginning of school from home during pandemic Covid-19. It was conducted from May until June 2020 with 30 millennial mothers born in the 1980s to 1999 in Indonesia. Millennial mothers experienced positive feelings (confidence, satisfaction, happiness) and negative feelings (burden, shock, frustration, stress, and depression). The child experienced positive feelings (happiness, satisfaction, enjoyment) and negative feelings (missing school, tiredness, stress, and sadness). The study results show that negative feelings are determined by negative thoughts caused by mothers’ communication when accompanying their children studying online. Therefore, mothers need to improve how they communicate with their children in school and at home to deal with negative emotions.